NILAI PENDIDIKAN KARAKTER DALAM TARI MESEKAT PADA MASYARAKAT ALAS DI KABUPATEN ACEH TENGGARA - HILZHA - FEBRINA (Gesture: Jurnal Seni Tari, 2021)
ABSTRACT - Meusekat dance is one of the dances in Southeast Aceh Regency, specifically the Alas community, which is staged as an entertainment dance for them. Meusekat dance provides many lessons for the community in living their lives which can be observed from the dance composition, musical accompaniment, floor patterns that are part of their appearance. Based on this, this research was conducted to see the value of character education in the lives of the Alas people. The analysis uses Asmani's theory (2011: 36-40) which suggests 5 values of character education, namely 1) the value of character education in relationships with God, 2) the value of character education in relationships with oneself, 3) the value of character education in relationships with others, 4) the value of education. character of the relationship with the natural surroundings/environment, and 5) the value of character education in relation to nationality. Of these five values, four values are used except the value of character education in relation to the natural environment/environment. The samples in this study were community leaders and dancers from the Bekhudihe studio. Data collection techniques using qualitative analysis. From the results of this study, there are values of character education seen from dance elements ranging from motion, poetry and clothing according to the Meusekat dance which refers to each character education value in the Alas community in Southeast Aceh Regency.Keyword:Value, Character Education, Mesekat Dance   ABSTRAK - Tari Meusekat merupakan salah satu tari yang ada di Kabupaten Aceh Tenggara, tepatnya pada masyarakat Alas, yang dipentaskan sebagai tari hiburan bagi mereka. Tari Meusekat memberikan banyak pelajaran-pelajaran bagi masyarakat dalam menjalani kehidupannya yang dapat diamati dari susunan tarian, iringan musik, pola lantai yang menjadi bagian dari penampilannya. Berdasarkan hal tersebut penelitian ini dilakukan untuk melihat Nilai pendidikan karakter yang ada didalamnya dalam kehidupan masyarakat Alas. Analisis menggunakan teori Asmani (2011: 36-40) yang mengemukakan 5 nilai pendidikan karakter yaitu 1) nilai pendidikan karakter hubungan dengan Tuhan, 2) nilai pendidikan karakter hubungan dengan diri sendiri, 3) nilai pendidikan karakter hubungan dengan sesama, 4) nilai pendidikan karakter hubungan dengan alam sekitar/lingkungan, dan 5) nilai pendidikan karakter hubungan dengan kebangsaan. Dari kelima nilai ini, digunakan empat nilai kecuali nilai Pendidikan karakter hubungan dengan alam sekitar/lingkungan. Sampel dalam penelitian ini adalah tokoh masyarakat dan penari sanggar Bekhudihe. Teknik pengumpulan data menggunakan analisis kualitatif. Dari hasil penelitian ini terdapat nilai pendidikan karakter yang dilihat dari elemen tari mulai dari gerak, syair dan busana sesuai pada tari Meusekat yang mengacu kepada masing-masing nilai pendidikan karakter pada masyarakat Alas di Kabupaten Aceh Tenggara. Kata Kunci : Nilai, Pendidikan Karakter, TariMesekat